PERANAN PENTINGNYA PERILAKU BERSEDEKAH TERHADAP KEBAHAGIAAN PADA DONATUR LEMBAGA ZAKAT INFAQ SHADAQAH BINA INSANI (LAZISBI) SEMARANG - Husna Ulfatunnisa’ Azzahro; Siska Adinda Prabowo Putri; Brigitan Argasiam (IMAGE, 2023)
This study aims to examine whether there is a correlation between the tendency to give charity to happiness. The samples used were Lazisbi Semarang donors, totaling 270 people. The sampling technique used is simple random sampling. The analysis used is spearman rank correlation. The instrument used on the donor's happiness variable is based on the theory of aspects of happiness from Seligman while the almsgiving behavior tendency variable uses a alms measuring instrument scale in an Islamic perspective. The results of this study indicate that there is a positive and significant relationship between happiness and the tendency to give alms, there is a value of rs = 0.469 (p <1%). The percentage level of donor happiness variable and charity behavior tendency variable is included in high categorization, donor happiness variable reaches 87.41% and charity behavior tendency variable reaches 90.37%. In this study, there was an effective contribution of 20.5% and the remaining 80.5% came from other factors outside the focus of this study.